Long term NIV in an infant with Hallermann-Streiff syndrome: A case report and overview of respiratory morbidity - Guerin, S; Blanchon, S; de Halleux, Q; Bayon, V; Ferry, T (Frontiers in Pediatrics, 2022)
Hallermann-Streiff syndrome (HSS) is a rare congenital syndrome with different anomalies including midface hypoplasia, beak nose and micrognathia. The upper airways narrowness can lead to severe respiratory complications such as obstructive sleep apnoea syndrome (OSAS), particularly in infancy. The management of these severe OSAS is difficult and poorly documented in literature. We report the case of an infant with HSS complicated by severe and early OSAS successfully managed with non-invasive ventilation (NIV), provide an overview of respiratory morbidities and discuss treatment options for HSS-related OSAS.